1975
DOI: 10.1037/0022-006x.43.5.637
|View full text |Cite
|
Sign up to set email alerts
|

Influence of motivational variables on the reactivity and reliability of self-recording.

Abstract: Three experiments that investigated variables related to the assessment and therapeutic functions of self-recording are reported. In Experiment 1, 20 college students in a classroom situation were differentially reinforced (successfully) either for increments in agreement between their self-recorded frequency of face touching and the frequencies reported by trained observers or for decrements in face touching. In Experiment 2, 21 college students in a classroom situation received varying levels of verbal feedb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 21 publications
3
29
0
Order By: Relevance
“…Another explanation for the difference between the Interview and Diary is that the monitoring of one's own behavior may alter the observed behavior, but this is more likely to occur if there is a positive or negative value associated with the behavior (Kazdin 1974). For instance, cigarette use has been shown to increase during self-monitoring (McFall 1970), but the self-monitored number of cigarettes used per week did not vary among subjects unmotivated to quit smoking (Lipinski et al 1975). We did not enquire about participants' motivation to reduce their caffeine intake, but it is unlikely that the diary was biased by a general reactivity to self-monitoring since there was no difference between the Interview and Diary results for the low and moderate users.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the difference between the Interview and Diary is that the monitoring of one's own behavior may alter the observed behavior, but this is more likely to occur if there is a positive or negative value associated with the behavior (Kazdin 1974). For instance, cigarette use has been shown to increase during self-monitoring (McFall 1970), but the self-monitored number of cigarettes used per week did not vary among subjects unmotivated to quit smoking (Lipinski et al 1975). We did not enquire about participants' motivation to reduce their caffeine intake, but it is unlikely that the diary was biased by a general reactivity to self-monitoring since there was no difference between the Interview and Diary results for the low and moderate users.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of self-monitoring to increase desired behaviors is attributed to its reactive effects on targeted behaviors (Anderson & Wheldall, 2004;Broden, Hall, & Mitts, 1971;Cavalier, Ferretti, & Hodges, 1997;Gottman & McFall, 1972;Hayes & Nelson, 1983;Kirby, Fowler, & Baer, 1991;Korotitsch & Nelson-Gray, 1999;Lipinski, Black, Nelson, & Ciminero, 1975;McLaughlin, 1976;Nelson & Hayes, 1981;Snider, 1983). Reactivity is defined as the effect that self-monitoring has on the frequency of targeted behavior as a function of the self-monitoring procedure (Kanfer, 1970;Nelson & Hayes, 1981;Rachlin, 1974).…”
Section: Reactivity Of Self-monitoringmentioning
confidence: 99%
“…Interestingly, a number of studies have demonstrated that self-recorders are more accurate in their recordings when they are aware their accuracy is being monitored by external observers. 15,16,17 Thus, it is possible that an advantageous side effect in having parents observe their children's headaches is that the children may take greater care to rate pain intensity accurately knowing that someone else is also rating it.…”
Section: Formentioning
confidence: 99%